1997
DOI: 10.3109/03005364000000005
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Management of Benign Paroxysmal Positional Vertigo by Exercise Therapy and by Repositioning Manoeuvres

Abstract: Benign paroxysmal positional vertigo (BPPV) is a common condition that often resolves spontaneously, but can cause significant distress to a patient. Management of this condition includes no intervention, medication, surgery, physical exercises and more recently 'particle repositioning' manoeuvres. Repositioning manoeuvres aim to relocate free-floating particles from the posterior semicircular canal into the utricle where they will no longer cause vertiginous symptoms. This article describes the different exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…The Dix Hallpike Maneuver (DHM) is the test most commonly used to induce signs and symptoms of BPPV, and is regarded as the gold standard and critical for accurate diagnosis 54. It is illustrated in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dix Hallpike Maneuver (DHM) is the test most commonly used to induce signs and symptoms of BPPV, and is regarded as the gold standard and critical for accurate diagnosis 54. It is illustrated in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The DHM is not 100% sensitive due to the nature of BPPV which cycles through acute and clinically silent phases. If a patient is examined during a sub-clinical period, symptoms and signs may not be provoked 5455. In addition, an appraisal of the literature has revealed that estimates of specificity are lacking 54.…”
Section: Methodsmentioning
confidence: 99%
“…and vertigo based on repeat Dix-Hallpike test and improve balance based on repeat computerized platform testing (19,(22)(23)(24), but 8-14% of patients may still complain of imbalance (9,25,26). Benyon (26) has postulated that this imbalance may be due to persistent BPPV that is not sufficient to deflect the cupula during testing or may be due to vestibular hypofunction that was not detected during the initial evaluation. We do not believe that the persistent imbalance is due either of these problems.…”
Section: Persistent Imbalance In Patients With Remission From Bppvmentioning
confidence: 97%
“…Because the Dix-Hallpike test and the CRT require that the head be rotated 45 degrees and extended [20][21][22][23][24][25][26][27][28][29][30] degrees, this test and treatment should not be performed in patients with certain types of neck disorder. Humphriss et al (3) considers the following disorders as absolute contraindications to performing the test and presumably the treatment: history of neck surgery, recent neck trauma, severe rheumatoid arthritis, atlantoaxial and occipitoatlantal instability, cervical myelopathy or radiculopathy, carotid sinus syncope, Chiari malformation, and vascular dissection syndromes.…”
Section: Contraindications To the Assessment And Treatment Of Bppvmentioning
confidence: 99%
“…The cupula will therefore be displaced abnormally, and neural firing will result. For a review of these hypotheses, and of treatment options for BPPV, the reader is referred to Beynon (1997).…”
Section: Introductionmentioning
confidence: 99%